Social representations of old age and retirement in the Nurse's view (Research, Society and Development, 2020)
Objective: to present the social representations of aging in the world of work for elderly and adult nursing professionals. Method: research with a qualitative approach based on social representations. 36 nursing professionals aged between 27 and 67 years old, of both sexes, participated in a university hospital located in the State of Rio de Janeiro. The semi-directive interview was used to collect data and the Alceste 4.9 software was used to process the transcribed material for data analysis. Results: the program presented a specific category for the retirement of the nursing professional as a social representation of old age. This representation of old age interferes with the attitude or decision to retire or not. Conclusion: the nursing professional is little prepared to face the moment of retirement and that managers need to pay attention to this reality.